Innovative Strategies to Enhance Cricket Farming Productivity through the Use of Environmental Monitoring Technology in Pamulang, South Tangerang City - Putra, Alifi Restu; Jannah, Dita Miftakhul; Alfarisi, Sya'ban Maulana; Sutariyono, Sutariyono; Tohiroh, Tohiroh (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
Cricket farming in Indonesia, particularly in Pamulang, South Tangerang City, has seen significant growth. However, productivity is often hampered by a lack of effective environmental monitoring, particularly regarding temperature, humidity, and lighting. This research aims to develop an innovative strategy to increase cricket farming productivity through the application of digital environmental monitoring technology. This tool is used to read environmental conditions in real time, allowing farmers to intervene or maintain optimal environmental conditions for cricket growth and development. The method in this research is a qualitative method with case studies, while data collection is done by surveys, interviews, direct observation, and analysis of data recorded from environmental monitoring tools consisting of temperature, humidity, room lighting, and focus group discussions (FGD). The results of the study show that environmental monitoring was carried out at 3 points, namely the middle, east and west of the cage, as well as three measurement times, namely morning, noon, and evening with a sampling of 30 measurements, found non-ideal conditions, namely air temperature ranging from 29.70°C - 34.10°C and lighting ranging from 25.1 Lux - 217 Lux, while humidity is still in the ideal category ranging from 60% - 70%, but with environmental monitoring the conditions can be immediately addressed and become ideal. From these results, it can increase cricket productivity by 15%, this is also supported by the results of interviews with cricket farmers. The impact of this research can contribute to cricket farmers, especially in Pamulang and Indonesia in general in increasing cricket productivity by using environmental monitoring tools, while for researchers it can be more innovative and technology-based integrated in subsequent research.